Religion and Violence: A Protestant Christian Perspective - Ariarajah, S. Wesley (Journal of ecumenical studies, 2017)
The article discusses the use of religion in conflict associated with social, economic, and political motivations of the terrorists. It highlights the basic teachings of religious traditions which may serve for violent tendencies. It also cites the differences between Christians and Jews in terms of alienation between God and human beings and nature.